The Ly49 Gene Family. A Brief Guide to the Nomenclature, Genetics, and Role in Intracellular Infection - Schenkel, Alan R.; Kingry, Luke C.; Slayden, Richard A. (Frontiers in Immunology, 2013)
Understanding the Ly49 gene family can be challenging in terms of nomenclature and genetic organization. The Ly49 gene family has two major gene nomenclature systems, Ly49 and Killer Cell Lectin-like Receptor subfamily A (klra). Mice from different strains have varying numbers of these genes with strain specific allelic variants, duplications, deletions, and pseudogene sequences. Some members activate NK lymphocytes, invariant NKT lymphocytes and γδ T lymphocytes while others inhibit killing activity. One molecule, Ly49Q, is not found on NK cells at all, rather is expressed only on myeloid cells. There is growing evidence that these receptors may regulate not just the immune response to viruses, but other intracellular pathogens as well. Thus, this review's primary goal is to provide a guide for researchers first encountering the Ly49 gene family and a foundation for future studies on the role that these gene products play in the immune response, particularly the response to intracellular viral and bacterial pathogens.